Societal awareness of environmental certifications in Costa Rica - Valenciano-Salazar, Jorge A. (2021)
The effectiveness of voluntary environmental programs and certifications to render social and private benefits depends on how aware consumers are, so that they can consider such initiatives when making their decisions. Consumers’ awareness has been mostly addressed in developed countries, although the benefits of companies’ environmental actions also take place in developing countries. This study is conducted in a developing country, such as Costa Rica. Using a large sample (n = 1191), consumers’ awareness of environmental certifications is studied at a general level (being able to name some environmental certification or program) and at a specific level (ability to name certified firms). The results show that consumers who are younger, with higher household income, with a university or technical degree and those participating in environmental or community groups are more likely to be aware of environmental certifications on both levels. Moreover, aware consumers tend to be more willing to pay for a certified coffee or a coffee produced by a certified company.